Investigation of Dielectric Barrier Discharge Plasma for the Degradation of Erythromycin Solution - Yifan Liu; Xiaolong Wang; Zongzheng Wang; Tianao Xv; Xiaowen Dai; Yadi Liu; Ying Sun; Tong Zhao; Yuantao Zhang (Molecules)
Antibiotic contamination constitutes a serious environmental and public health risk. In order to fill the gap in the study of plasma degradation of erythromycin (ERY), this paper systematically investigated the mechanism of ERY degradation by dielectric barrier discharge (DBD) plasma. The underlying reaction mechanisms were investigated by experiments and molecular dynamics simulations. Plasma emission spectra revealed active hydroxyl radicals (·OH) and argon (Ar) spectral lines. The degradation efficiency of plasma treatment for ERY was found to be strongly influenced by treatment parameters, including applied voltage, treatment duration, and gas flow rate. In particular, a maximum degradation of 90% was achieved for a 250 mg/L ERY solution under conditions of 18 kV voltage, 850 sccm gas flow rate, and 60 min of treatment. The presence of ·OH and hydrogen peroxide (H2O2) in the reaction and their important role in the degradation were proved experimentally. Fracture of the ERY lactone ring induced by hydrogen abstraction reactions with reactive oxygen species (ROS) was observed by molecular dynamics simulations. In the in vitro antimicrobial assays targeting Staphylococcus aureus, the treated solutions demonstrated low toxicity, underscoring the practical applicability of dielectric barrier discharge (DBD) plasma technology in addressing antibiotic contamination in aquatic environments.